Pengaruh PAD, Belanja Modal, dan Penerimaan Pembiayaan terhadap Pengeluaran Pemerintah di Provinsi DKI Jakarta - Agmirsya, Dwilita; Dewi, Eva Sherlina; Pamungkas, Agustina Anantalia; Septiani, Yustirania (WELFARE Jurnal Ilmu Ekonomi, 2024)
This study aims to analyze and evaluate the extent of the influence of Regional Original Revenue (PAD), Capital Expenditure, and Regional Financing Receipts on the Government Expenditure of Jakarta Province. The data used in this study is secondary time-series data covering the period from 2015 to 2022, sourced from One Data Jakarta Province. Data analysis was conducted using a quantitative approach through multiple linear regression model equations. The results of the study indicate that, simultaneously (F-test), PAD, capital expenditure, and regional financing receipts significantly influence the government expenditure of Jakarta Province. Partially, Regional Original Revenue (PAD) and Regional Expenditure have a positive and significant impact on the Government Expenditure of Jakarta Province. Meanwhile, Regional Financing Receipts have a negative and significant effect on the Government Expenditure of Jakarta Province. The implications of these findings suggest that the local government is expected to maximize regional expenditures that support efforts to enhance and strengthen the potential of PAD in DKI Jakarta Province.Penelitian ini bermaksud untuk menganalisis dan mengevaluasi sejauh mana pengaruh dari Pendapatan Asli Daerah (PAD), Belanja Modal, dan Penerimaan Pembiayaan Daerah terhadap Pengeluaran Pemerintah Provinsi Jakarta. Data yang digunakan dalam penelitian ini adalah data sekunder time series rentang periode tahun 2015–2022 bersumber dari Satu Data Provinsi Jakarta. Analisis data dilakukan dengan pendekatan kuantitatif melalui persamaan model regresi linier berganda. Hasil penelitian menunjukkan bahwa secara simultan (uji F) PAD, belanja modal dan penerimaan pembiayaan daerah berpengaruh signifikan terhadap pengeluaran pemerintah Provinsi Daerah Jakarta. Secara parsial Pendapatan Asli Daerah (PAD) dan Belanja Daerah memiliki pengaruh positif dan signifikan terhadap Pengeluaran Pemerintah Provinsi Jakarta. Penerimaan Pembiayaan Daerah berpengaruh negatif dan signifikan terhadap Pengeluaran Pemerintah Provinsi Jakarta. Implikasi dari hasil penelitian ini, pemerintah setempat diharapakan mampu memaksimalkan belanja daerah yang mendukung upaya peningkatan  dan memperkuat potensi PAD Provinsi DKI Jakarta.